Magnetohydrodynamic Simulation of a Coronal Mass Ejection Observed during the Near-radial Alignment of Solar Orbiter and Earth - Talwinder Singh; Dinesha V. Hegde; Tae K. Kim; Nikolai V. Pogorelov (The Astrophysical Journal)
Interplanetary coronal mass ejections (ICMEs) are the primary sources of geomagnetic storms at Earth. The negative out-of-ecliptic component ( B _z ) of magnetic field in the ICME or its associated sheath region is necessary for it to be geoeffective. For this reason, magnetohydrodynamic simulations of CMEs containing data-constrained flux ropes are more suitable for forecasting their geoeffectiveness as compared to hydrodynamic models of the CME. ICMEs observed in situ by radially aligned spacecraft can provide an important setup to validate the physics-based heliospheric modeling of CMEs. In this work, we use the constant-turn flux rope (CTFR) model to study an ICME that was observed in situ by Solar Orbiter (SolO) and at Earth, when they were in a near-radial alignment. This was a stealth CME that erupted on 2020 April 14 and reached Earth on 2020 April 20 with a weak shock and a smoothly rotating magnetic field signature. We found that the CTFR model was able to reproduce the rotating magnetic field signature at both SolO and Earth with very good accuracy. The simulated ICME arrived 5 hr late at SolO and 5 hr ahead at Earth, when compared to the observed ICME. We compare the propagation of the CME front through the inner heliosphere using synthetic J-maps and those observed in the heliospheric imager data and discuss the role of incorrect ambient solar wind background on kinematics of the simulated CME. This study supports the choice of the CTFR model for reproducing the magnetic field of ICMEs.